2017
DOI: 10.1093/icesjms/fsx164
|View full text |Cite
|
Sign up to set email alerts
|

Regional-scale patterns in harbour porpoise occupancy of tidal stream environments

Abstract: As harbour porpoises Phocoena phocoena are abundant within tidal stream environments, mitigating population-level impacts from tidal stream energy extraction is considered a conservation priority. An understanding of their spatial and temporal occupancy of these habitats at a regional-scale will help steer installations towards locations which maximize energy returns but reduce the potential for interactions with populations. This study quantifies and compares relationships between the presence of harbour porp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In near-shore coastal regions, marine mammals and seabirds frequently forage within tidally active areas (Nol and Gaskin, 1987;Marubini et al, 2009;Anderwald et al, 2012;Benjamins et al, 2015;Warwick-Evans et al, 2016;Waggitt et al, 2018), resulting in distinct regularities in their distributions and behaviours that coincide with particular tidal phases (Becker et al, 1993;Irons, 1998;Isojunno et al, 2012;De Boer et al, 2014;Ijsseldijk et al, 2015). Specifically, areas such as narrow channels, headlands, islands, reefs and bays often function as periodic foraging hotspots, where interactions between strong tidal currents (often exceeding 1.5ms -1 ) and complex topography create prosperous foraging opportunities for marine predators (Cairns and Schneider, 1990;Coyle et al, 1992;Zamon, 2003;Benjamins et al, 2015;Couperus et al, 2016).…”
Section: Channels Headland and Island Wakes Nearshore Reefs And Baysmentioning
confidence: 99%
“…In near-shore coastal regions, marine mammals and seabirds frequently forage within tidally active areas (Nol and Gaskin, 1987;Marubini et al, 2009;Anderwald et al, 2012;Benjamins et al, 2015;Warwick-Evans et al, 2016;Waggitt et al, 2018), resulting in distinct regularities in their distributions and behaviours that coincide with particular tidal phases (Becker et al, 1993;Irons, 1998;Isojunno et al, 2012;De Boer et al, 2014;Ijsseldijk et al, 2015). Specifically, areas such as narrow channels, headlands, islands, reefs and bays often function as periodic foraging hotspots, where interactions between strong tidal currents (often exceeding 1.5ms -1 ) and complex topography create prosperous foraging opportunities for marine predators (Cairns and Schneider, 1990;Coyle et al, 1992;Zamon, 2003;Benjamins et al, 2015;Couperus et al, 2016).…”
Section: Channels Headland and Island Wakes Nearshore Reefs And Baysmentioning
confidence: 99%
“…The site-specific and spatiotemporally variable distributions of porpoises in energetic tidal areas (Gordon et al 2011, Benjamins et al 2017, across tidal state, emphasizes the value of understanding occupancy patterns when conducting risk assessments (Scott et al 2014, Waggitt et al 2017a. For example , Macaulay et al (2015) showed varying porpoise behaviours at 3 different tidal rapid sites in Scotland, with regard to both depth distribution and swim direction relative to the current.…”
Section: Patterns In Acoustic Detections In Relation To Environmentalmentioning
confidence: 99%
“…Previous studies (e.g. Hastie et al 2016, Macaulay et al 2017, Waggitt et al 2017a have investigated marine mammal habitat use and behaviours in tidal areas in the absence of any tidal energy infrastructure. While such knowledge is relevant given that collision risk depends on animal density and diving behaviour (Hastie et al 2014), these studies did not measure avoidance behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Santos & Pierce, 2003; but see Nielsen et al 2018). Coined the ‘aquatics shrews’ of the sea, prey availability has been shown to be an important driver of porpoise movements (Johnston et al, 2005; Sveegaard et al, 2012; Wisniewska et al, 2016) and local densities (Hammond et al, 2013; Marubini et al, 2009; Waggitt et al, 2018). These animals are thus expected to be highly susceptible to environmental changes, increasing sea temperature, and prey displacements or modifications (Lambert et al, 2014; MacLeod et al, 2005).…”
Section: Introductionmentioning
confidence: 99%